Isolated pulmonary valve endocarditis: truth or myth? - Siamak M. Seraj; Evanpaul Gill; Simranjit Sekhon (Greater Baltimore Medical Center, 2017)
Pulmonary valve (PV) infective endocarditis (IE) is an extremely rare disease that involves normal as well as abnormal valves. This condition mostly occurs in patients with underlying predisposing factors. It could be missed if patients do not present with typical features of right-sided endocarditis or in the absence of classic risk factors. The case presented here did not have any known risk factors for IE until surgery and presented mainly with fever, weight loss, and musculoskeletal symptoms.